American Phenomenology
XXXI, 447 p.
Keywords: THEODORE KISIEL Date of birth: October 30,1930. Place of birth: Brackenridge, Pennsylvania. Date of institution of highest degree: PhD. , Duquesne University, 1962. Academic appointments: University of Dayton; Canisius College; Northwestern University; Duquesne University; Northern Illinois University. I first left the university to pursue a career in metallurgical research and nuclear technology. But I soon found myself drawn back to the uni versity to 'round out' an overly specialized education. It was along this path that I was 'waylaid' into philosophy by teachers like H. L. Van Breda and Bernard Boelen. The philosophy department at Duquesne University was then (1958-1962) a veritable "little Louvain," and the Belgian-Dutch connection exposed me to (among other visiting scholars) Jean Ladriere and Joe Kockelmans, who planted the seeds which eventually led me to the hybrid discipline of a hermeneutics of natural science, and prompted me soon after graduation to make the first of numerous extended visits to Belgium and Germany. The endeavor to learn French and German led me to the task of translating the phenomenological literature bearing especially on natural science and on Heidegger. The talk in the sixties was of a "continental divide" in philosophy between Europe and the Anglo-American world. But in designing my courses in the philosophy of science, I naturally gravitated to the works of Hanson, Kuhn, Polanyi and Toulmin without at first fully realizing why I felt such a strong kinship with them, beyond their common anti positivism.